Effects of Sodium-Glucose Cotransporter 2 Inhibitors on Water and Sodium Metabolism - Tang, Jun; Ye, Lifang; Yan, Qiqi; Zhang, Xin; Wang, Lihong (Frontiers in Pharmacology, 2022)
Sodium-glucose cotransporter 2 (SGLT2) inhibitors exert hypoglycemic and diuretic effects by inhibiting the absorption of sodium and glucose from the proximal tubule. Currently available data indicate that SGLT2 inhibitors transiently enhance urinary sodium excretion and urinary volume. When combined with loop diuretics, SGLT2 inhibitors exert a synergistic natriuretic effect. The favorable diuretic profile of SGLT2 inhibitors may confer benefits to volume management in patients with heart failure but this natriuretic effect may not be the dominant mechanism for the superior long-term outcomes observed with these agents in patients with heart failure. The first part of this review explores the causes of transient natriuresis and the diuretic mechanisms of SGLT2 inhibitors. The second part provides an overview of the synergistic effects of combining SGLT2 inhibitors with loop diuretics, and the third part summarizes the mechanisms of cardiovascular protection associated with the diuretic effects of SGLT2 inhibitors.